Optimization of Edge Termination Techniques for β-Ga2O3 Schottky Rectifiers. (2nd December 2019) - Sharma, Ribhu; Patrick, Erin E.; Law, M. E.; Ren, F.; Pearton, S. J.
Abstract : To realize the potential of Gallium oxide (Ga2 O3 ) Schottky rectifiers fabricated for high voltage and fast switching applications, various edge termination techniques to maximize the breakdown voltage (Vbr ) are studied and examined via simulations using the FLOODS/FLOOPS TCAD simulator. The simulated Schottky rectifiers consist of a Si-doped (n = 1.0 × 10 15 – 1.3 × 10 17  cm −3 ) β-Ga2 O3 epitaxial layer grown on Sn-doped (n = 4.8 × 10 18  cm −3 ) Ga2 O3  substrates. The optimization of field plate geometry for Schottky barrier diodes (SBD) was investigated using the device breakdown characteristics as the figure-of-merit. Various field plate dielectrics (SiO2, SiNx, Al2 O3, and HfO2 ) were explored while the field plate structure was concurrently varied to obtain a normalized breakdown field (VNbr ) of ∼3 for a step (graduated form) dielectric with Al2 O3 as the dielectric. Edge termination via the formation of resistive areas at the anode contact periphery via ion (argon) implantation was also examined for the SBDs since other edge termination techniques are ineffective due to lack of p-type doping in Ga2 O3 . The configuration of the implanted region was investigated and a VNbr of over 5 was achieved for diodes with an unbounded resistive region and an implantation depth of 50–100 nm.